2009
DOI: 10.1080/10508400902797958
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Learning in Groups: Analyzing Equity in Two Cooperative Activity Structures

Abstract: Many mathematics classrooms use cooperative learning to support equitable learning environments for all students. Past research in the field has focused primarily on increasing achievement, rather than contexts that support equitable interactions. This year-long study in three secondary mathematics classes compares two activity structures-a group quiz and a presentation-by examining group interaction within the two activities. The analysis shows that groups constructed a range of work practices, including a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 34 publications
1
76
0
1
Order By: Relevance
“…We began with Esmonde's four categories [5] but quickly found that we needed to expand the number of categories in order to capture the nuances of the interactions endemic to our classroom. We developed the categories recursively.…”
Section: Methods and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…We began with Esmonde's four categories [5] but quickly found that we needed to expand the number of categories in order to capture the nuances of the interactions endemic to our classroom. We developed the categories recursively.…”
Section: Methods and Participantsmentioning
confidence: 99%
“…As we analyzed our video data, we came to realize that every studentstudent or student-instructor interaction involves some degree of inequality. The degree of inequality will determine how much access less confident students have to critical semiotic resources in the classroom [5]. For example, afraid of showing her lack of understanding, a student may choose to watch other group members construct a ray diagram on a whiteboard as opposed to actively helping the group to draw the diagram.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one disadvantage of the study group is equality in the distribution of tasks. Expert in the group tended to dominate interactions during group activities (Esmonde, 2009). Aside from that, studies of Cronin and McCabe (2017) showed negative result of by group activity.…”
Section: International Journal Of Research Studies In Education 93mentioning
confidence: 99%
“…These analytic memos built up towards the sections of the argument in this paper, since they tended to focus attention on aspects of the world under examination which contributed to cultural construction of engineering ability. These interpretations were continually discussed amongst the research team and with other colleagues at research meetings for considering alternative interpretations for increased robustness of the argument, via a process of iterative refinement of hypotheses 23 . Triangulation (or crystallization) of diverging data sources and interpretations was important to the analytic process; so for example, a student quote was not taken at face value but used as a guiding orientation to the holistic consideration of the dataset.…”
Section: Methodological Overviewmentioning
confidence: 99%